Pengembangan Media Pembelajaran Game - Based Learning (GBL) Berbantuan Baamboozle Pada Materi Penjumlahan Matriks Kelas XI SMA Negeri 2 Sekayam - Yohana Fransiska Yohana; Syarifah Fadillah; Muchtadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aims to develop a Game-Based Learning (GBL) educational medium using Baamboozle for the matrix addition curriculum in the 11th grade at SMA Negeri 2 Sekayam. The background of this study is the limited use of innovative and interactive educational media in mathematics instruction, resulting in suboptimal student engagement and motivation. This study employed the Research and Development (R&D) method using a modified 4D development model (3D), namely Define, Design, and Develop. The research subjects consisted of subject matter experts and media experts, as well as 24 11th-grade students at SMA Negeri 2 Sekayam as product test subjects. Data collection techniques included validation sheets, student response questionnaires, and a posttest. The results showed that the Baamboozle-assisted GBL learning media achieved a validity rate of 84.99%, meeting the “highly valid” criterion, comprising 83.33% from subject matter expert validation and 86.66% from media expert validation. The media’s practicality, as determined by the student response questionnaire, reached 87.14%, meeting the “highly practical” criterion. Meanwhile, the effectiveness level of the media, based on the results of the student posttest, was 75%, meeting the “effective” criterion. Based on these results, the Baamboozle-assisted Game-Based Learning (GBL) instructional media for the matrix addition material for 11th-grade students at SMA Negeri 2 Sekayam is declared valid, practical, and effective. Keywords: Game-Based Learning (GBL), Baamboozle, educational media, matrix addition.